2005
DOI: 10.1038/sj.emboj.7600712
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 3, a stress sensor, activates p53 by blocking its ubiquitination

Abstract: Activating transcription factor 3 (ATF3) is rapidly induced by diverse environmental insults including genotoxic stress. We report herein that its interaction with p53, enhanced by genotoxic stress, stabilizes the tumor suppressor thereby augmenting functions of the latter. Overexpression of ATF3 (but not a mutated ATF3 protein (D102-139) devoid of its p53-binding region) prevents p53 from MDM2-mediated degradation and leads to increased transcription from p53-regulated promoters. ATF3, but not the D102-139 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
249
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(273 citation statements)
references
References 43 publications
19
249
5
Order By: Relevance
“…These results suggest that HA and NMH induced the same oxidative stress and SIPS via similar (Kang et al 2000), induction of apoptosis (Chung et al 2003) Increase Apoptosis BCL2-associated X protein BAX Pro-apoptotic proteins (Adams and Cory 1998), mitochondrial dysfunction (Gross et al 1998 Activating transcription factor 3 ATF3 Maintaining DNA integrity and protecting against cell transformation (Yan et al 2005) Increase oxygen toxicities, because both conditions have the same oxygen partial pressure. Moreover, the expressions of proteins involved in heat shock and cell cycle check points were not significantly different between the two hyperoxic conditions.…”
Section: Discussionmentioning
confidence: 87%
“…These results suggest that HA and NMH induced the same oxidative stress and SIPS via similar (Kang et al 2000), induction of apoptosis (Chung et al 2003) Increase Apoptosis BCL2-associated X protein BAX Pro-apoptotic proteins (Adams and Cory 1998), mitochondrial dysfunction (Gross et al 1998 Activating transcription factor 3 ATF3 Maintaining DNA integrity and protecting against cell transformation (Yan et al 2005) Increase oxygen toxicities, because both conditions have the same oxygen partial pressure. Moreover, the expressions of proteins involved in heat shock and cell cycle check points were not significantly different between the two hyperoxic conditions.…”
Section: Discussionmentioning
confidence: 87%
“…These genes may also be target genes of HIF-1, since all genes encoding glycolytic enzymes as well as many other metabolic genes were upregulated by hypoxia in a HIF-1-dependent manner. 33 Atf3, which stabilizes p53 tumor suppressor, 34 was upregulated by gold-1a. In addition, the expression of Mmp13 was reported to be dysregulated during cancer progression associated with p53 inactivation, 35 but this gene was down- regulated in response to gold-1a.…”
Section: Discussionmentioning
confidence: 99%
“…ATF3 has been suggested to be critical in metastasis, and has also been reported to be proapoptotic as well as antiapoptotic (Ishiguro and Nagawa, 2000;Hai and Hartman, 2001;Francis et al, 2004;Hartman et al, 2004). As this paper was Anoxic induction of ATF3 K Ameri et al completed, it was reported that ATF3 stabilizes p53 upon genotoxic stress (Yan et al, 2005), and also induces tubulogenic differentiation in endothelial cells and angiogenesis in diabetic angiopathy (Okamoto et al, 2006). Thus, a potential role of ATF3 in modulating p53 and angiogenesis under anoxia should be investigated.…”
mentioning
confidence: 86%